2020
DOI: 10.3390/jcm9103338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Evolocumab on Vulnerable Coronary Plaques: A Serial Coronary Computed Tomography Angiography Study

Abstract: This study investigated the effects of evolocumab on vulnerable coronary plaques and factors associated with the change in stability and size of plaques in patients taking statins. Vulnerable coronary plaques were defined using coronary computed tomography (CT) angiography as having a density of <50 HU within the region of interest and a remodeling index ≥1.1. The changes in minimum CT density, remodeling index, and percent stenosis of vulnerable coronary plaques after six months of evolocumab administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“… 82–84 Similar results were found in a study using serial CCTA imaging. 85 Both icosapent ethyl and colchicine have also shown to result in reductions in low-density or non-calcified plaque using serial CCTA ( Table 3 ). 86–89 …”
Section: The Role Of Coronary Computed Tomography Angiography In Pati...mentioning
confidence: 99%
“… 82–84 Similar results were found in a study using serial CCTA imaging. 85 Both icosapent ethyl and colchicine have also shown to result in reductions in low-density or non-calcified plaque using serial CCTA ( Table 3 ). 86–89 …”
Section: The Role Of Coronary Computed Tomography Angiography In Pati...mentioning
confidence: 99%
“…remodeling index and minimum CT value improved in patients whose LDL-C was controlled around 19 mg/dL after 6 months of lipid-lowering therapy; these findings were not observed in patients whose LDL-C was controlled to 69 mg/dL. 30 Therefore, to reduce lipid volume in patients with large LRCP, the target LDL-C must be as low as possible. Patients with a larger lipid arc at the non-culprit lesion on baseline OCT, especially an arc >154°, must be treated with aggressive lipid-lowering therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, stabilizing and regressing atherosclerotic plaque are primary objectives in ASCVD management. Previous trials have shown promising results in delaying plaque development using statins, evolocumab, low-dose colchicine, and icosapent ethyl [22][23][24][25]. However, the effect of SGLT2i [27,28].…”
Section: Modi Cation Of Atherosclerotic Plaquementioning
confidence: 99%